Ubiquinol supplementation protects against renal ischemia and reperfusion injury in rats - W. Peerapanyasut (2018)
Generation of toxic oxygen metabolites followed by oxidant- and inflammatory-mediated tissue injury plays a crucial role in the pathogenesis of ischemia and reperfusion (IR). Ubiquinol, the reduced form of coenzyme Q10, is recognized for its potent antioxidant and anti-inflammatory properties in biological membranes. The present study was established to examine the possible protective effect of ubiquinol against renal IR injury. Groups of male Wistar rats were assigned into sham, ubiquinol, IR (45-min bilateral renal ischemia followed by 24-h reperfusion), and ubiquinol+ IR (ubiquinol 300 mg/kg given orally for 7 consecutive days before IR induction). Renal morphology, function, oxidative stress, and inflammatory markers were evaluated at the end of reperfusion. IR caused renal dysfunction as shown by significant increases in blood urea nitrogen, plasma creatinine, and a decrease in creatinine clearance. Light and electron microscopic examinations exhibited severe tubular damages and abnormal mitochondrial structure. IR-induced renal injuries were associated with significant increases in malondialdehyde, nitric oxide, tumor necrosis factor-α, but decreases in antioxidant thiols and superoxide dismutase. Pretreatment with ubiquinol obviously attenuated all the changes caused by IR, whereas it had no considerable effect in the sham-operated rats. These findings indicate that supplementation of ubiquinol prior to IR incidence confers functional and morphological protection to the ischemic kidney by maintaining the redox balance and regulating the generation of inflammatory mediator. The outcomes suggest that ubiquinol may be a potential candidate to counteract organ dysfunction in conditions involving IR injury. © 2013 Informa UK, Ltd.